PENGARUH ORAL HYGIENE PADA WANITA PASKAMENOPAUSE DENGAN KEJADIAN GINGIVITIS PADA KELOMPOK WANITA TANI (KWT) DI KECAMATAN LUBUK ALUNG KABUPATEN PADANG PARIAMAN - Hidayati Hidayati; Rima Semiarty; Winerli Septevani (Andalas Dental Journal, 2013)
Menopause is the end of menstruation cycle and reproduction period for women. A woman is entering postmenopausal if she doesn’t get menstruation for 12 months or more. As menopause, estrogen and progesteron hormone decreased. Decrease of progesteron and estrogen level followed by clinical change in oral cavity which gets risk gingivitis and influence oral hygiene. This study aims to know the relation between oral hygiene of postmenopausal women and the incidence of gingivitis in Kelompok Wanita Tani (KWT) in Kecamatan Lubuk Alung Kabupaten Padang Pariaman. The design of this study is the Cross Sectional Study. This study was conducted to 53 postmenopausal women in Kelompok Wanita Tani in Kecamatan Lubuk Alung Kabupaten Padang Pariaman in Desember 2012. The data was collected through questionnaires and examinations of OHIS index and gingival index by chi-square analysis. The results showed that the majority (43,4%) postmenopausal women in Kelompok Wanita Tani had a moderate oral hygiene and also (45,3%) had a moderate of gingivitis. The gum looks pale or red about (75,5%) and easy to bleed about (56,6%). All of postmenopausal women in Kelompok Wanita Tani in Kecamatan Lubuk Alung Kabupaten Padang Pariaman got gingivitis althought they had good oral hygiene